Garlic (Allium sativum L.): a potential unique therapeutic food rich in organosulfur and flavonoid compounds to fight with COVID-19 - Sucheta Khubber; Reza Hashemifesharaki; Mehrdad Mohammadi; Seyed Mohammad Taghi Gharibzahedi (Nutrition Journal, 2020)
Abstract Coronavirus disease 2019 (COVID-19) is the current major health crisis in the world. A successful strategy to combat the COVID-19 pandemic is the improvement of nutritional pattern. Garlic is one of the most efficient natural antibiotics against the wide spectrum of viruses and bacteria. Organosulfur (e.g., allicin and alliin) and flavonoid (e.g., quercetin) compounds are responsible for immunomodulatory effects of this healthy spice. The viral replication process is accelerated with the main structural protease of SARS-CoV-2. The formation of hydrogen bonds between this serine-type protease and garlic bioactives in the active site regions inhibits the COVID-19 outbreak. The daily dietary intake of garlic and its derived-products as an adjuvant therapy may improve side effects and toxicity of the main therapeutic drugs with reducing the used dose.